Against Consilience: Outsider Scholarship and the Isthmus Theory of Knowledge Domains. - King, Mike (Integral Review: A Transdisciplinary & Transcultural Journal for New Thought, Research, & Praxis, 2013)
The endless proliferation of human knowledge within sub-disciplines represents not so much a tree structure of knowledge from which we can stand back and admire some organic unity as the tentacles of an octopus dragging us down into anguished division. The anguish is genuine and has been expressed since the Enlightenment by many types of thinker. This paper argues however that the anguish does not in fact arise from the nature of human knowledge but from the mistaken belief in the possibility of its unification. The desire for the unitive has been erroneously transplanted from its proper context - the mystical - to the domain of knowledge, as the latter - particularly under the rubric of "science" - has become the only culturally legitimised stance towards the world. Conventional scholarship, while busy creating sub-branches and sub-sub-branches on which the leaves of new knowledge sprout with vigour and abandon, is powerless to avoid this feeling of anguish. It feels compromised in the thwarted longing for a lost sense unity. "Outsider scholarship" - of the type practiced by Koestler, Schumacher and Pirsig - is often preoccupied with just this question, but is free to propose various taxonomies of knowledge, often of an unfashionably hierarchical kind, that cut across conventional boundaries and which provide a basis for an uncompromised relationship with knowledge. This paper starts with a brief consideration of outsider scholarship, including its anachronistic characteristics, and then turns to Pirsig's meditation on the technologies behind the word-processor, which lead to an "isthmus theory of knowledge domains." It then considers Steven Jay Gould's non-overlapping magisteria, and the hint from Ken Wilber about epistemological pluralism. These are then used to show why E. O. Wilson's consilience is misguided: it represents the final triumph of logical positivism - a takeover bid for the humanities by the sciences - but couched in terms apparently irresistible to fashionable thought.